Managing hours of work and rest breaks: a Malaysian perspective - Ashari, Hapriza; Soehod, Khairiah; Nik Mahmod, Nik Ahmad Kamal (Man In India, 2017)
This paper critically analyses the provisions of the law regulating hours of work and rest breaks in Malaysia. It explores and examines crucial legal issues on the subject and analyse judicial judgements on related disputed matters. The key statutory provision that prescribes the law is governed by section 60A of the Malaysian Employment Act 1955. The principal focus of this paper is on the legal rights and protection that the law provides pertaining to working time limits and rest breaks. The legal analysis includes the topic on the daily working time limit, weekly working time limit, daily work spread over a period of ten hours and the right to in-work rest breaks. In addition, the analysis will look into the statutory exemptions to the working time limit and also explain the legal definitions of hours of work and normal hours of work.